Cdc2 Kinase-dependent Disassembly of Endoplasmic Reticulum (ER) Exit Sites Inhibits ER-to-Golgi Vesicular Transport during Mitosis - Kano, Fumi (The American Society for Cell Biology, 2004)
We observed the disassembly of endoplasmic reticulum (ER) exit sites (ERES) by confocal microscopy during mitosis in Chinese hamster ovary (CHO) cells by using Yip1A fused to green fluorescence protein (GFP) as a transmembrane marker of ERES. Photobleaching experiments revealed that Yip1A-GFP, which was restricted to the ERES during interphase, diffused throughout the ER network during mitosis. Next, we reconstituted mitotic disassembly of Yip1A-GFP–labeled ERES in streptolysin O-permeabilized CHO cells by using mitotic L5178Y cytosol. Using the ERES disassembly assay and the anterograde transport assay of GFP-tagged VSVGts045, we demonstrated that the phosphorylation of p47 by Cdc2 kinase regulates the disassembly of ERES and results in the specific inhibition of ER-to-Golgi transport during mitosis.